World Affairs Education: Past Experience, Culture, and Meaning Making - Susan Yelch Biniecki; Simone C.O. Conceição (Adult Education Research Conference, 2008)
This paper describes adult learners' lived experiences as participants in world affairs educational programs; how they make meaning of content and delivery; and how past experience, culture, and meaning making affect program choice. Findings suggest that looking at individuals’ past and present experiences provide insight into participants’ cultural lenses.
Keywords: cultural meaning making; world affairs; diversity development